IMPLEMENTASI PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN BARANG MILIK NEGARA DI PENGADILAN NEGERI SAMBAS - Sugeng Sujono; Ida Rochamawati; Sugilar (FISIP Universitas Malikussaleh, 2026)
This study aims to analyze the implementation of Good Governance principles in the management of State-Owned Assets at the Sambas District Court, which still faces administrative challenges, weak control mechanisms, and inconsistencies in record-keeping. The research employed a qualitative descriptive method using in-depth interviews, observations, and document reviews involving court leaders and asset management staff. Data were analyzed through the stages of reduction, presentation, and conclusion drawing. The findings indicate that the principle of the rule of law has been implemented based on Government Regulation No. 27 of 2014 and Minister of Finance Regulation No. 181 of 2016, although its execution is still hindered by technical constraints. Transparency is realized through the use of State Asset Management Information System, Agency-Level Financial Application System, and Electronic State Asset Development and Enchancement Work Aplication, yet remains suboptimal due to limited access and data update consistency. Effectiveness and efficiency have begun to be applied but are constrained by limited resources. Accountability is carried out through regular audits and reporting, although some asset coding errors persist. In conclusion, the implementation of Good Governance principles is underway but not yet fully optimal.